PERANCANGAN VIDEO PROMOSI CANDI-CANDI DI TROWULAN SEBAGAI UPAYA MENGENALKAN WISATA SEJARAH MOJOKERTO - Tamalanrea, Alpha Dian; Yurisma, Dhika Yuan; Cinantya, Ixsora Gupita (Jurnal Art Nouveau, 2018)
The temples in Trowulan is a relic of the Majapahit kingdom that is still preserved and has a very interesting charm to visit. However, every year the temples in Trowulan have decreased tourists. Therefore, the authors designed a promotional video as an effort to introduce the temples in Trowulan. The research method used qualitative method with data collection technique using observation, interview, documentation, literature and existing. The concept used is "historical". The concept of "historical" to showcase the cultural heritage that can be the biggest historical tourist attraction in Mojokerto. This concept will be applied to any design that includes video and other supporting media